Anti-staling of high-moisture starchy food: Effect of hydrocolloids, emulsifiers and enzymes on mechanics of steamed-rice cakes. (October 2018) - Ai, Jing; Witt, Torsten; Cowin, Gary; Dhital, Sushil; Turner, Mark S.; Stokes, Jason R.; Gidley, Michael J.
Abstract: High-moisture rice snacks, such as steamed rice cakes, develop firmness on storage which decreases shelf life significantly. By analogy with lower moisture bread systems, this staling was hypothesised to be due to a combination of starch retrogradation and moisture re-distribution. Therefore, food additives which are commonly used to retard starch retrogradation during bread staling, including enzymes, hydrocolloids and emulsifiers (alpha-amylase, alginate, xanthan, guar gum, carrageenan, carboxymethyl cellulose, distilled monoglyceride, and sodium stearoyl lactylate) were investigated for their anti-hardening effects in high-moisture rice snacks. The results showed that only alginate significantly reduced the firming rate of rice cakes. However, differential scanning calorimetry measurements surprisingly indicated that rice cakes with alginate had higher levels of starch retrogradation than the control after storage for 7 days. Magnetic resonance imaging results were characterised by a redistribution of signal intensity from the edge to the centre of rice cakes and the formation of high intensity regions. These features were stronger with the addition of alginate. We propose that the alginate forms a continuous phase with water that has high mobility, whereas the partially gelatinized starch granules are an included phase distributed within the continuous phase. The reduced hardness of aged rice cakes with alginate is more dependent on the soft continuous phase than the hard starch granules, therefore leading to a softer texture. This mechanism is different to that proposed to operate for lower water content baked systems, therefore hydrocolloid and other anti-staling agents which are effective in bread systems may not be applicable in higher moisture starchy foods. Graphical abstract: Image 1 Highlights: Effects of anti-staling treatments used in baking evaluated for steamed rice cakes. Alginate showed the most effective anti-firming effect but promoted starch retrogradation. Anti-firming mechanism proposed to be due to structuring of the soft continuous phase. Hydrocolloid anti-staling mechanisms are different for high and low moisture foods.